2016
DOI: 10.11604/pamj.2016.25.66.8532
|View full text |Cite
|
Sign up to set email alerts
|

Facteurs prédictifs du fonctionnement chez les patients bipolaires de type 1 en période de rémission

Abstract: IntroductionLes études récentes indiquent que le trouble bipolaire est associé à une déficience profonde dans presque tous les domaines de fonctionnement. La présente étude vise à évaluer le fonctionnement au sein d'une population de patients bipolaires type I en rémission.MéthodesIl s'agit d'une étude transversale réalisée auprès des patients bipolaires type I euthymiques et suivis en ambulatoire. Ont été utilisés l'échelle de dépression de Hamilton, l'échelle de manie de Young, l'Echelle d'Estime de Soi de R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Previous studies have found that manic episodes were associated with poor occupational functioning, 46 and previous depressive episodes were associated with poor job performance 38,47 . Similar to the findings of our study, several studies have found that previous depressive episodes have a negative impact on general functioning, 48,49 while other studies have reported the adverse effects of manic episodes on functioning 50,51 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous studies have found that manic episodes were associated with poor occupational functioning, 46 and previous depressive episodes were associated with poor job performance 38,47 . Similar to the findings of our study, several studies have found that previous depressive episodes have a negative impact on general functioning, 48,49 while other studies have reported the adverse effects of manic episodes on functioning 50,51 …”
Section: Discussionsupporting
confidence: 89%
“…38,47 Similar to the findings of our study, several studies have found that previous depressive episodes have a negative impact on general functioning, 48,49 while other studies have reported the adverse effects of manic episodes on functioning. 50,51 Subthreshold symptoms are purportedly the most consistent predictors of level of functioning across studies. 51 Low levels of subthreshold depressive symptoms can influence functional outcomes, and previous evidence has shown that functional impairment increases significantly with each step up in depressive symptom severity.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of functional impairment in BD is heterogeneous and has consistently been associated with residual depressive symptoms and/or cognitive impairment in crosssectional studies (Baş et al, 2015;Samalin et al, 2016Samalin et al, , 2017Sanchez-Moreno et al, 2018). In addition, a lower level of functioning has been associated to male gender, older age, unemployment, a higher number of previous mood episodes and of hospitalizations, psychiatric comorbidities, sleep disorders or higher emotional reactivity (Fekih-Romdhane et al, 2016;Murru et al, 2018;Sanchez-Moreno et al, 2018).…”
Section: Introductionmentioning
confidence: 99%